Pentingnya Penataan Arsip dalam Menunjang Aktivitas Kerja Karyawan Bidang PSU pada Dinas Perumahan dan Kawasan Permukiman serta Pertanahan Kabupaten Deli Serdang - Panca Syahputra; Muhammad Ikhsan Harahap (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Archives that are well managed will really help a company/organization. Every company/organization requires data and information, one of the sources of which comes from archives/documents. Therefore, managing archives must be implemented correctly to achieve the goal of helping the company's work program to achieve work targets. However, there are still some companies/organizations that take records management for granted. Negligence in managing records will result in employees trying to find the records they need being hampered and slowing down employee work effectiveness. This research was carried out in the field of infrastructure, facilities and public utilities at the office of the Housing and Residential Areas and Land Affairs of Deli Serdang Regency. The method used is descriptive qualitative with data sources obtained by direct observation. The results of this research explain how archives are organized to support employee activities.